Global cassava research and development: The cassava economy of Asia: Adapting to economic change - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Cassava is a regional crop in India, 97 percent of the production coming from the states of Kerala and Tamil Nadu. On a countrywide basis, cassava makes only a small contribution to total calorie intake; in the south, however, it ranks 2nd to rice. Data are presented on production and utilization trends and distribution, production systems, yields, production costs, and labor utilization. Highlights are given of technology research and development being done by the Central Tuber Crops Research Institute in Kerala and by the Tamil Nadu Agricultural Univ. in Coimbatore and the Tapioca Expt. Station in Salem District. Markets and demand are different; while fresh cassava for human consumption is demanded in Kerala, starch or tapioca pearls are demanded in Tamil Nadu. Dried cassava chips for human consumption are also produced in Kerala on a limited scale. As regards pricing and market efficiency, rice prices have declined, putting a damper on prices for cassava. The implications of the foregoing are discussed in terms of the potential for cassava to meet the food needs of the poor, which would not involve subsidies from the government, as is required in the case of rice. (CIAT)